Fronteiras da migração: geopolítica e narrativas de mulheres venezuelanas na Paraíba - Lopes, Daniela Lustosa (2021)
With the increase in Venezuelan immigration to Brazil, whose peak was in 2018, the brazilian government had to face a situation that demanded an immediate response in order to support those crossing the borders, as well to manage the situation along the state of Roraima, the main spot of entrancy caused by the northern border with Venezuela. That was how Operação Acholhida began, whose action plan contained National Interiorization Program. In this sense, the paper aims to investigate the particularities of the migratory process of venezuelan women, and in which way it has an impact on the reach of citizenship and the fulfillment of human rights, especially through the insertion in the labour world. Thus, it builds a geopolitical overview for understanding the roots of venezuelan migratory reasons that aims to give an overview of the roots of Venezuelan migratory motivations and the context in which Brazil found itself for the reception of these people. Analyzes national public policies directed at this population from 2018 and the form adopted for territorialization. Reflects on narratives of venezuelan women living in Paraíba and the construction of territoriality. The theoreticalmethodological way was based on the critical theory of knowledge in line with the approach of cultural geography in its humanistic perspective. It is an interdisciplinary research based on decolonial thinking, especially in Quijano (2005), Mignolo (2005; 2017) and Lugones (2014). The concepts of territory, deterritorialization, territoriality and borders were worked from Haesbaert (2004), Bonnemaison (2002) and Raffestin (1993); for the historical aspects of Brazil and Venezuela, Santos (2020), Souza (2016), Amenta (2010) and Maringoni (2009) were used; as for oral history, it was based mainly on Magalhães (2017); on migration and female mobility, Moreira (2019), Stolz (2014, 2017), Dulce (1999, 2007) and Silva (2017) were used; finally, the Operação Acolhida was studied from Pacific and Silva (2019). It is based on qualitative data and bibliographic-documentary research. In addition, it is anchored in fieldwork with semistructured interviews with three venezuelan women and with three representatives of organizations in the migratory sphere in the state of Paraíba. It was concluded that, despite being scarce, the national and international legislative apparatus recognizes violence against women in the migratory process as a violation of human rights. The resistance and courage shown in the narratives of Venezuelan women in field research are also a result of the violence they are subjected to, such as silencing, arduoness in accessing work, the restriction of working in certain areas and the document bureaucracy that needs to be dealt with, become an obstacle to the guarantee of other rights. Therefore, specific public policies for these women are necessary, in order to provide instruments for the achievement of their rights. In addition, the research pointed out the importance of the political-social study involving Venezuelan migration, so that the study does not become depoliticized and becomes stuck with aspects of violence, as a remedy. In Paraíba, the National Interiorization Program, has proven to be essential for the insertion of these people into Brazilian society.